Karakterisasi dan Stabilitas Fisik Mikroemulsi Tipe A/M dengan Berbagai Fase Minyak - Fitriani, Endang Wahyu; Imelda, Erlina; Kornelis, Christina; Avanti, Christina (Pharmaceutical Sciences and Research, 2016)
This research consists of formulation, characterization and physical stability of the microemulsion of water-in-oil type. On the microemulsion, VCO, palm oil, olive oil and soybean oil were used as oil phase, aqua demineralisata used as the aqueous phase, a combination of Span® 80 and Tween® 80 as a surfactant and propanol as cosurfactant. Each formula was three times replication done and determined the physical characteristics including organoleptic observations, measurements of density, droplet, viscosity, flow properties, and pH. Determination of physical characteristics was done at the beginning of the microemulsion formed and after 5 weeks storage at room temperature. The physical stability test including the centrifugation test at 10,000 rpm for 30 minutes, the freeze-thaw test for 6 cycles, and heating stability with the oven temperature of 60ºC, 70ºC, 80ºC, 90ºC and 100ºC for 5 hours were done. The data obtained were analyzed using t-Test and one-way ANOVA. Based on the characteristic and physical stability tests, it was showed that microemulsion with VCO, palm oil and soybean oil had better physical characteristics and stability compared to the microemulsion with olive oil.